A proposito di Noi - Lenzini, Luca (L’ospite ingrato, 2022)
Alessandro Broggi’s research constitutes one of the most stimulating cases in the context of contemporary literary experiences. With a genuine cognitive imprint, in Noi – his most recent work – writing goes beyond traditional distinctions and genres to define limits and horizons of experience, declining in collective terms an itinerary inside of Nature, according to the model of the journey into the unknown. But moving away from the social and sharing sphere, it is the language that is imbued with fragments, modules and citations, designating a sphere of the possible carved into the repertoire of current discourse, with results of great impact on the reader.